Bank stock return reactions to the COVID-19 pandemic: The role of investor sentiment in MENA countries - Mohamed Al-Baity; Ray Saadaoui Mallek; Hasan Mustafa (Risks, 2022)
In this study, we investigated the impact of COVID-19 investor sentiment (CS), number of cases (CC), and deaths (CD) on bank stock returns in 16 MENA countries. In addition, we examined the interaction effects of CS with CC and CD on bank stock returns. Lastly, we looked at whether Islamic banks outperformed conventional banks during the pandemic. Based on monthly data from the Middle East and North Africa (MENA) countries from February 2020 to July 2021, we used the clustered standard error fixed effect estimation on Islamic and conventional bank stock market returns. The results suggest that CC and CD have negative impacts on bank stock market returns while CS has no effect, except for the lagged value. The interaction effect of CS with CC and CD on stock returns proved to strengthen the link in the current month and weaken the link in the previous month.
Keywords: G01; G10; G15; 330; bank return; COVID-19; Islamic banks; MENA countries